2009
DOI: 10.1038/modpathol.2008.182
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EGFR abnormalities in patients with pulmonary adenocarcinoma: the need to test neoplasms with more than one method

Abstract: Patients with advanced pulmonary adenocarcinoma exhibiting overexpression or mutation of epidermal growth factor receptor tend to respond better to targeted therapy with tyrosine kinase inhibitors such as gefitinib and erlotinib. There is no consensus regarding how these neoplasms should be routinely tested for epidermal growth factor receptor (EGFR) and whether the results of immunohistochemistry (IHC), mutation analysis and fluorescent in situ hybridization correlate with each other or are independent predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 18 publications
3
46
0
1
Order By: Relevance
“…Such selection of patients with NSCLC promoted a better treatment strategy for both high and low EGFR mutations abundant tumors. [30][31][32][33] Further quantification of staining scores in mutation-positive NSCLC has been assessed, and high staining score has been associated with a significant longer progression-free survival in mutation-positive patients as compared with low staining score. 31 A study in which the randomization to EGFR tyrosine kinase inhibitors would be based on the method used for demonstrating an activating EGFR mutation might give clinical relevant information regarding the significance of the amount of EGFR-mutated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such selection of patients with NSCLC promoted a better treatment strategy for both high and low EGFR mutations abundant tumors. [30][31][32][33] Further quantification of staining scores in mutation-positive NSCLC has been assessed, and high staining score has been associated with a significant longer progression-free survival in mutation-positive patients as compared with low staining score. 31 A study in which the randomization to EGFR tyrosine kinase inhibitors would be based on the method used for demonstrating an activating EGFR mutation might give clinical relevant information regarding the significance of the amount of EGFR-mutated cells.…”
Section: Discussionmentioning
confidence: 99%
“…40 The lack of gene amplification does not entirely exclude the role of EGFR inhibitors in the treatment of metastasizing adnexal carcinomas; as there are conflicting results in the literature regarding the role of IHC, FISH, and/or PCR in treatment decision of various tumors. [41][42][43] There is frequent discrepancy between the EGFR protein expression and gene amplification in other tumors in the literature. 44 Furthermore, inconsistent results have also been reported regarding the correlation between EGFR gene mutations and EGFR gene amplification/ polysomy detected by FISH (Bell et al, 2005;Sone et al, 2005).…”
mentioning
confidence: 99%
“…44 Furthermore, inconsistent results have also been reported regarding the correlation between EGFR gene mutations and EGFR gene amplification/ polysomy detected by FISH (Bell et al, 2005;Sone et al, 2005). In a recent series of 100 patients with advanced pulmonary adenocarcinoma, Gupta et al 41 proposed that tumors should be evaluated by more than one method to identify patients that may benefit from tyrosine kinase inhibitors therapy.…”
mentioning
confidence: 99%
“…Previous studies have reported a correlation between levels of EGFR protein expression and gene mutation with poor prognosis and reduced survival rates of lung cancer (Sanja et al, 2006;Ekrem et al, 2010). In non-small cell lung cancer, overexpression of EGFR or mutations in intracellular EGFR have been observed in 43-89% of cases (Gupta et al, 2009). These mutations occur within EGFR exons 18-21 (Soh et al, 2009;Baek et al, 2014).…”
Section: 233 Overexpression Of Egfr Protein In Bruneian Lung Cancersmentioning
confidence: 99%